KI67 AS A SURROGATE MARKER FOR MITOTIC KARYORRHECTIC INDEX IN NEUROBLASTOMA - Javed, Rabia; Mushtaq, Sajid; Akhtar, Noreen; Hassan, Usman; Loya, Asif (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the use of Ki67 as a surrogate marker for Mitotic Karyorrhectic Index (MKI) in Neuroblastoma. Study Design: Cross-sectional study. Place and Duration of Study: This was a retrospective study conducted at Department of Histopathology, Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan. 41 cases of neuroblastoma from 2010 to 2014 were retrieved. Methodology: Forty one cases of neuroblastoma were evaluated. Clinical and morphological features like age, gender and subtype of tumor were quantified. For each case, Mitotic Karyorrhectic Index was calculated and categorized as low, intermediate and high. This was followed by immunostaining for Ki67 on each case. Using linear regression model an equation was derived to calculate ki67 from Mitotic Karyorrhectic Index. The equation was as follows: Mitotic Karyorrhectic Index = (Ki67 x 0.115) ± 1.355. Using this equation, the cut-off values for low, intermediate and high Ki67 were <5.60%, 5.60% - 23.0% and >23.0% respectively. Results: Twenty four cases had low Mitotic Karyorrhectic Index and in 18/24 cases, Ki67 was also low. There were 5 cases with intermediate Mitotic Karyorrhectic Index with two cases showing correspondingly intermediate Ki67 index. There were 12 cases with high Mitotic Karyorrhectic Index and 10/12 cases showed a high Ki67 index as well. Conclusion: Ki67 is a useful technique and may be used as an adjunct to Mitotic Karyorrhectic Index for better evaluation of cases.